2009
DOI: 10.1002/ange.200804937
|View full text |Cite
|
Sign up to set email alerts
|

Synthese, Struktur und Komplexierungseigenschaften von partiell und vollständig reduziertenmeso‐Octamethylporphyrinogenen (Calix[4]pyrrolen)

Abstract: Aus alt mach neu: Calixpyrrole sind bekannte Anionenbinder und können nur schwer in Übergangsmetallkomplexe überführt werden. Die vollständige Hydrierung eines Calixpyrrols ergab nun einen Liganden, der leicht klassische Kupfer‐, Nickel‐ und Palladiumkomplexe bilden kann. Die Metallkomplexe enthalten ein Netzwerk von vier ausgerichteten Wasserstoffbrücken, die spezifisch Gegenionen binden (siehe Bild; blau N, weiß H, grün Cl, rot Cu, Ni oder Pd).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For the synthesis of (II), 2,2 0 -(propane-2,2-diyl)bis(1H-pyrrole), (I) (Journot, Letondor et al, 2010;Blangy et al, 2009) (5.00 g, 29 mmol), 10% Pd/C (1.30 g), methanol (20 ml) and acetic acid (2 ml) were placed in an autoclave vessel. The reaction was kept under hydrogen (50 atm; 1 atm = 101 325 Pa) and stirred at room temperature for 20 h. The reaction mixture was then filtered through a pad of Celite and washed three times with dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of (II), 2,2 0 -(propane-2,2-diyl)bis(1H-pyrrole), (I) (Journot, Letondor et al, 2010;Blangy et al, 2009) (5.00 g, 29 mmol), 10% Pd/C (1.30 g), methanol (20 ml) and acetic acid (2 ml) were placed in an autoclave vessel. The reaction was kept under hydrogen (50 atm; 1 atm = 101 325 Pa) and stirred at room temperature for 20 h. The reaction mixture was then filtered through a pad of Celite and washed three times with dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
“…In order to study the selectivity of the hydrogenation (monohydrogenation versus total hydrogenation) and to compare the hydrogenation conditions of the dipyrromethane 2,2 0 -(propane-2,2-diyl)bis(1H-pyrrole), (I) , with the hydrogenation conditions of calix[4]pyrrole (Blangy et al, 2009;Journot, Letondor et al, 2010), the synthesis and crystal structure of the partially reduced compound 2-[2-(pyrrolidin-2-yl)propan-2-yl]-1Hpyrrole, (II), were studied. During efforts to modify partially reduced calix[4]pyrroles (Blangy et al, 2009;Journot, Letondor et al, 2010) by introducing amides on the pyrrolidine rings, unforeseen difficulties were encountered.…”
Section: Commentmentioning
confidence: 99%
“…Calix [4]pyrrolidine 1 [12] (80 mg, 0.18 mmol, 1 equiv.) and MnA C H T U N G T R E N N U N G (OAc) 2 ·4 H 2 O (44 mg, 0.18 mmol, 1 equiv.)…”
Section: General Procedures For the Preparation Of Mn Complexes 2 Andmentioning
confidence: 99%
“…During our studies of the hydrogenation of calix [4]pyrroles we were able to isolate the fully reduced porphyrinogen macrocycle 1 (Scheme 1), able to function as a non-porphyrin ligand for metal binding. [12] Although fully saturated, this novel tetraaza-macrocycle shows a "disc-like", almost planar conformation in the crystal. The four basic nitrogen atoms were shown to function as efficient chelating ligands for transition metals such as Cu, Ni, Pd, with the four pyrrolidine N À H bonds pointing in a parallel direction orthogonal to the plane of the disk.…”
Section: Introductionmentioning
confidence: 99%
“…Calixpyrroles can bind anions efficiently (Sessler et al, 2000), but they coordinate transition metals only under forcing conditions (Jubb et al, 1992;Floriani, 1996;Bonomo et al, 2001). Recently we reported on the partial and complete reduction of meso-octamethylporphyrinogen, or calix [4]pyrrole as it is called (Blangy et al, 2009;Journot et al, 2010). It was found that the reduced form of calix[4]pyrrole, i.e.…”
Section: Introductionmentioning
confidence: 99%